Optimizing performance and health: Nutrition considerations for female athletes in strength and conditioning - Cabre, H. E. (Strength and Conditioning Journal, 2025)
Nutrition and dietary intake are key factors for exercise and sport performance. While a substantial body of research highlights the impact of nutrition on exercise, many dietary and nutrient recommendations are based on research studies only conducted in men. However, the distinct physiological, neurological, and hormonal changes across a woman's life cycle significantly affect nutritional needs. This narrative review explores key recommendations for calories, carbohydrates, fats, proteins, and select supplements, highlighting the absence of sex-specific guidelines in current dietary frameworks for strength and conditioning female athletes. The review synthesizes current literature to provide practical guidance for coaches, sport dietitians, and health practitioners to optimize both performance and health outcomes for female athletes.